Efeitos adjuvantes da fibrina rica em plaquetas injetável (i-PRF) na terapia periodontal não cirúrgica: Ensaio clínico, controlado e randomizado de boca dividida - Alves, Roberta de Oliveira (2024)
Objective: To evaluate the effects of injectable platelet-rich fibrin (i-PRF) application as an adjunct therapy to scaling and root planing (SRP) in patients with periodontitis. Materials and Methods: Twenty-four patients with two pairs of contralateral teeth with probing depths ≥ 5 mm were included in the study. The pairs of teeth were randomized into two treatment groups: the control group (n = 149 sites) (SRP alone) and the test group (n = 135 sites) (SRP + i-PRF). Clinical periodontal parameters including probing depth (PD), gingival recession (GR), clinical attachment level (CAL), plaque index (PI), and full-mouth bleeding on probing (fBOP) were evaluated at baseline, 45 and 90 days. The distance from the cementoenamel junction to the alveolar bone crest (CEJ-BC) was analyzed using periapical radiographs at baseline and at 90 days. Results: Both groups exhibited decreasing on PD, CAL, fBOP, and PI values from baseline to 45 days, with no significant difference between them (p > 0.05). GR increased on the test group at 45 days (p < 0.05). A reduction in CEJ-BC was observed in both groups at 45 days, with no significant difference (p < 0.05). At 90 days, no significant intra- or intergroup differences were noted for any of the parameters analyzed (p > 0.05). Conclusion: SRP alone and SRP + i-PRF as adjuncts promoted similar clinical and radiographic periodontal benefits.